Advance care planning in patients with advanced cancer: A 6-country, cluster-randomised clinical trial - Korfage, Ida J.; Carreras, Giulia; Arnfeldt Christensen, Caroline M.; Billekens, Pascalle; Bramley, Louise; Briggs, Linda; Bulli, Francesco; Caswell, Glenys; Červ, Branka; van Delden, Johannes J. M.; Deliens, Luc; Dunleavy, Lesley; et al. (PLoS medicine, 2020)
Advance care planning (ACP) supports individuals to define, discuss, and record goals and preferences for future medical treatment and care. Despite being internationally recommended, randomised clinical trials of ACP in patients with advanced cancer are scarce. To test the implementation of ACP in patients with advanced cancer, we conducted a cluster-randomised trial in 23 hospitals across Belgium, Denmark, Italy, Netherlands, Slovenia, and United Kingdom in 2015-2018. Patients with advanced lung (stage III/IV) or colorectal (stage IV) cancer, WHO performance status 0-3, and at least 3 months life expectancy were eligible. The ACTION Respecting Choices ACP intervention as offered to patients in the intervention arm included scripted ACP conversations between patients, family members, and certified facilitators; standardised leaflets; and standardised advance directives. Control patients received care as usual. Main outcome measures were quality of life (operationalised as European Organisation for Research and Treatment of Cancer [EORTC] emotional functioning) and symptoms. Secondary outcomes were coping, patient satisfaction, shared decision-making, patient involvement in decision-making, inclusion of advance directives (ADs) in hospital files, and use of hospital care. In all, 1,117 patients were included (442 intervention; 675 control), and 809 (72%) completed the 12-week questionnaire. Patients' age ranged from 18 to 91 years, with a mean of 66; 39% were female. The mean number of ACP conversations per patient was 1.3. Fidelity was 86%. Sixteen percent of patients found ACP conversations distressing. Mean change in patients' quality of life did not differ between intervention and control groups (T-score -1.8 versus -0.8, p = 0.59), nor did changes in symptoms, coping, patient satisfaction, and shared decision-making. Specialist palliative care (37% versus 27%, p = 0.002) and AD inclusion in hospital files (10% versus 3%, p < 0.001) were more likely in the intervention group. A key limitation of the study is that recruitment rates were lower in intervention than in control hospitals. Our results show that quality of life effects were not different between patients who had ACP conversations and those who received usual care. The increased use of specialist palliative care and AD inclusion in hospital files of intervention patients is meaningful and requires further study. Our findings suggest that alternative approaches to support patient-centred end-of-life care in this population are needed. ISRCTN registry ISRCTN63110516.